Penerapan Smart Laboratory Berbasis Internet of Things untuk Meningkatkan Keamanan dan Keselamatan di Laboratorium Komputer Universitas Muhammadiyah Pontianak - Fitri Wibowo; Suheri Suheri; Muhammad Hasbi; Neny Firdyanti; Budianingsih Budianingsih; Ferry Faisal; Yasir Arafat (I-Com: Indonesian Community Journal, 2024)
The Informatics Engineering Laboratory at Universitas Muhammadiyah Pontianak currently has not been equipped with monitoring system, posing a potential risk to user safety. This community service initiative aims to enhance security by implementing a smart laboratory system through the integration of Internet of Things (IoT) technology. The approach involves creating IoT sensor nodes and providing training to laboratory users. These sensor nodes, equipped with various sensors, monitor conditions like door status, smoke, and air quality. Data from these sensors is transmitted to a server and accessible via a web dashboard, enabling real-time online monitoring from any location. Consequently, the laboratory's monitoring capabilities are significantly enhanced, ensuring the safety of users. The implementation of an IoT-based smart laboratory system is crucial for safeguarding both the facility and its occupants, emphasizing the importance of technological advancements in maintaining a secure laboratory environment.